Bio-inspired synthesis of 3-D network of NiO-Ni nanowires on carbonized eggshell membrane for lithium-ion batteries. (2nd February 2019) - Meng, Xinghua; Deng, Da
Graphical abstract: Highlights: Composite nanowires of both metal oxide and metal nanoparticles successfully synthesized. 3D networks NiO-Ni nanowires attached on carbonized eggshell membrane. Precursor was synthesized on eggshell membrane in a diaphragm-assisted reactor. Eggshell membrane played multiple roles as bio-substrate and the source of reducing agents. 3D networks NiO-Ni nanowires attached on carbonized eggshell membrane demonstrated improved rate and cycling performances. Abstract: Composite nanowires incorporating both metal oxide and metal nanoparticles as the basic building units are attracting much attention recently. We report here a facile approach to synthesize 3D networks of 1D nanowires of formed by both NiO and Ni nanoparticle. The composite nanowires were in-situ synthesized on carbonized eggshell membrane. Here, α-Ni(OH)2 nanowire precursor was synthesized on eggshell membrane under mild conditions in a diaphragm-assisted reactor first. Then the precursor was transformed into composite of NiO-Ni nanowires on carbonized eggshell membrane under heat treatment in argon. The eggshell membrane played multiple roles as the substrate to collect the α-Ni(OH)2 nanowire precursor and then as the source of reducing agents to partially reduce Ni 2+ to Ni 0 . When tested for lithium-ion batteries, the composite of 3D networks NiO-Ni nanowires attached on carbonized eggshell membrane demonstrated impressively improved rate and cycling performances, as compared to that of bare NiO nanowires. The idea and method outline here based on bio-inspired synthesis using bio-template to prepare composites could be applied to synthesize other functional materials.